Prevalence of Sarcocystis infection in camels (Camelus dromedarius) slaughtered at Addis Ababa abattoir, Ethiopia - Mekbib, Berhanu (Journal of Science and Development, 2018)
Camels are very important animals for the livelihood of pastoralists in arid and semi-arid environments, but are highly neglected and poorly studied. A cross-sectional study was conducted from October 2018 to May 2019 to estimate the prevalence, associated risk factors and tissue distributions of Sarcocystis in one-humped camels slaughtered at Addis Ababa abattoir enterprise (Akaki branch). Esophagus, diaphragm and heart tissue samples were collected from 166 slaughtered camels and examined histopathologically for presence of Sarcocystis. Of the total camels examined, Sarcocysts were detected in 51 (30.72%) camels. Relatively higher proportions of males (33.33%), young ones (33.33%), those originated from Minjar (35.71%) and camels with good body condition (43.39%) had Sarcocystis infection compared to other categories. However, except for body condition score (p = 0.039), other considered risk factors did not show significant difference with the prevalence of Sarcocystis infection. The infection rate of esophagus, diaphragm and heart were 19.87%, 14.46% and 13.25%, respectively. Moreover, multiple tissue infections by this parasite were detected in 26 (51%) camels of the 51 Sarcocystis positive camels. In general, the observed high prevalence of camel Sarcocystis infection in the present study, coupled with lack of information on the public health and economic significance, warrants further investigation and community awareness creation about the control measures.